Enantioselective Radical Addition/Cross‐Coupling of Organozinc Reagents, Alkyl Iodides, and Alkenyl Boron Reagents. (28th August 2019) - Chierchia, Matteo; Xu, Peilin; Lovinger, Gabriel J.; Morken, James P.
Abstract: A hybrid transition‐metal/radical process is described that results in the addition of organozinc reagents and alkyl halides across alkenyl boron reagents in an enantioselective catalytic fashion. The reaction can be accomplished both intermolecularly and intramolecularly, providing useful product yields and high enantioselectivities in both manifolds. Abstract : Radikal‐Hybrid : Die Dicarbofunktionalisierung von VinylB(pin) gelang mit einem chiralen Nickel‐Katalysator. Unter Verwendung eines Alkylhalogenids und Organozink‐Reagentien wurden bei intra‐ oder intermolekularer Reaktionsführung hohe Enantioselektivitäten erzielt.